Detection of Vibrio vulnificus in Seafood With a DNAzyme-Based Biosensor - Fan, Shihui; Ma, Chao; Tian, Xiaopeng; Ma, Xiaoyi; Qin, Mingcan; Wu, Hangjie; Tian, Xueqing; Lu, Jing; Lyu, Mingsheng; Wang, Shujun (Frontiers in Microbiology, 2021)
Vibrio vulnificus is an important pathogenic bacterium that is often associated with seafood-borne illnesses. Therefore, to detect this pathogen in aquatic products, a DNAzyme-based fluorescent sensor was developed for the in vitro detection of V. vulnificus. After screening and mutation, a DNAzyme that we denominated “RFD-VV-M2” exhibited the highest activity, specificity, and sensitivity. The limit of detection was 2.2 x 103 CFU/mL and results could be obtained within 5 to 10 min. Our findings suggested that the target of DNAzyme RFD-VV-M2 was a protein with a molecular weight between 50 and 100 kDa. The proposed biosensor exhibited an excellent capacity to detect marine products contaminated with V. vulnificus. Therefore, our study established a rapid, simple, sensitive, and highly specific detection method for V. vulnificus in aquatic products.